Growth Performance of Merawangaranb Chickens with Different Genetic Composition - Harini, Nurcahya; Akbariyah, Ula Saffanah; S, Darwati (Universitas Nasional Jakarta, 2023)
Merawangarab chicken is a local chicken produced by two local chicken strain, namely merawang and arab chickens. This study aimed to analyze the growth of crosses between sixth generation merawangarab chickens with different genetic compositions of merawang (M) and arab (A) during 12 weeks of rearing. This research used the results of crossing Arabian chickens with Merawang chickens with different genetic ratios, namely 25% M, 50% M, 62.5% M, and 75% M. Variables included feed consumption, body weight, body weight gain, and feed conversion. The results of the research showed that the different genetic composition of the sixth generation of merawangarab chickens had no effect on the growth performance of the chickens during 12 weeks of rearing except for different feed consumption. Body weight at 12 weeks of age for each type of chicken were 856.8 ± 274.2 (23% M), 858.9 ± 195.4 (50% M), 863.7 ± 156.9 (62.5% M ), and 854.0±172.9 (75% M). The growth performance of the sixth generation of merawangarab chickens was still diverse and can be selected to improve the performance of merwangarab chickens.